An alternative sedation option for special care patients: combined inhalation sedation with nitrous oxide and oxygen and intravenous sedation with midazolam. (2nd July 2021) - Fenesan, Stephanie; Hughes, Sadie; Patel, Neha
Abstract : This article highlights an alternative sedation technique by providing inhalation sedation with nitrous oxide and oxygen alongside intravenous sedation with midazolam as an additional option for patients within special care dentistry. Two case reports are described, as well as a short overview of the available literature on this technique and the indications, advantages and disadvantages. This technique should be considered alongside other sedation techniques. As with all treatment for which sedation is provided, each case needs to be considered on an individual basis and the most appropriate option selected following discussion with the patient. CPD/Clinical Relevance: Although single sedation techniques provide a good level of sedation to facilitate dental treatment for the majority of patients, it is desirable to have an awareness of alternative sedation options that may be available for patients.